2017
DOI: 10.11138/mltj/2017.7.2.306
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the proximal patellar tendon attachment and its relationship to skeletal maturity in adolescent ballet dancersCharacterising the proximal patellar endon attachment and its relationship to skeletal maturity in adolescent ballet dancers

Abstract: SummaryBackground: It is unknown how and when the proximal attachment of the patellar tendon matures; puberty may be key in ensuring normal tendon formation. The aim of this study was to investigate the features of the proximal patellar tendon attachment at different stages of skeletal maturity, to help gain an understanding of how and when the tendon attachment matures. Methods: Sixty adolescent elite ballet students (ages 11-18) and eight mature adults participated. Peak height velocity (PHV) estimated skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Considering the age of the athletes participating in the present study, individual differences in biological maturity might have influenced the structural appearance of the tendon. Rudavsky et al (2017) reported a high variability of the echo patterns of the patellar tendons of young athletes before and around PHV and more consistent and continuous patterns similar to mature tendons after 1 year post-PHV. Such maturation-related structural changes would also affect the estimation of micromorphology as applied in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…Considering the age of the athletes participating in the present study, individual differences in biological maturity might have influenced the structural appearance of the tendon. Rudavsky et al (2017) reported a high variability of the echo patterns of the patellar tendons of young athletes before and around PHV and more consistent and continuous patterns similar to mature tendons after 1 year post-PHV. Such maturation-related structural changes would also affect the estimation of micromorphology as applied in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…In accordance with the previous study, Kubo et al (2014b) and Waugh et al (2012) reported that Achilles tendon Young’s modulus was lower in children (9–12 years) compared to adults, and junior high school students (13–15 years) had adult-like material properties. The mechanical changes observed from child- to adulthood may partly be mediated by an increase in the structural integrity of the collagenous network (Rudavsky et al, 2017, 2018). During pubertal growth, tendon length increases in a higher rate compared to the CSA, indicating that increments of tendon stiffness are mainly governed by a change of the material properties (Neugebauer and Hawkins, 2012; Waugh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly as adolescence is proposed to be a critical time for the formation of normal tendon attachment. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a key developmental period, with a mature proximal patellar tendon enthesis occurring after peak height velocity. 25 Given that patellar tendon structure is a predictor for pain, 26 it is reasonable to argue that caution should be exercised when treating patients with an immature enthesis. Training beyond pain in order to satisfy short-term sporting objectives could have negative long term implications for the individual.…”
Section: Discussionmentioning
confidence: 99%